Hepatic Artery Infusion of Floxuridine in Combination With Systemic Chemotherapy for Pancreatic Cancer Liver Metastasis: A Propensity Score-Matched Analysis in Two Centers - Peng, Changli; Xu, Bin; Xiao, Juxiong; Zhou, Chunhui; Li, Xiaodong; Shi, Hongbing; Qiang, Weiguang; Wang, Tianming; Zhao, Jiemin; Liu, Fei; Li, Gang; Li, Haiping; et al. (Frontiers in Oncology, 2021)
ABSTRACT Aim: To evaluate the efficacy of hepatic artery infusion (HAI) of floxuridine (FUDR) in combination with systemic chemotherapy in patients with pancreatic cancer liver metastases (PCLM). Patients and Methods: We retrospectively collected clinical data of 347 patients with PCLM who underwent first-line chemotherapy at 2 Chinese centers between 2012 and 2019. Propensity score matching between patients with and without HAI was performed to compensate for differences in baseline characteristics. Objective response rate (ORR) and overall survival (OS) between groups was compared. HAI pump functionality was recorded. Results: Data of 258 patients (62 patients with HAI and 196 patients without HAI) were used for matching. After 1:1 ratio matching, 62 patients per group were included. The intrahepatic ORR was 66.1% in HAI group and 22.6% in non-HAI group (P＜0.001), and the extrahepatic ORR was 25.0% versus 28.9% (P = 0.679). The median OS was significantly longer in HAI group (14.0 versus 10.8 months, P = 0.001). Multivariance COX regression showed HAI led to a decrease in hazard ratio for death by 61.8% (HR=0.382; 95% CI: 0.252-0.578; P ＜ 0.001). Subgroup analysis revealed that patients without EHM, with higher intrahepatic tumor burden and with synchronous liver metastasis benefited more from HAI. Dysfunction of HAI pump occurred in 5.7% of patients during the period of follow up. Conclusions: In patients with PCLM, first-line treatment with HAI FUDR plus SCT resulted in higher intrahepatic response and better OS.